Republic of Kosovo : Third Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Criterion. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
Kosovo's macroeconomic and financial policies have remained broadly on track. Progress continues to be made toward the key objectives, id est, restoring a sustainable fiscal position and sufficient government cash buffers, anchoring fiscal policy, and enhancing the resilience of the financial system. Careful preparation of social spending initiatives and fragile political environment remains key. The policies under the program provide the best safeguard to steer the economy through the period ahead, establish confidence in macroeconomic management, and lay the foundations for robust and balanced growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet